GENETIC, COLORATION, AND GROWTH PERFORMANCE OF TWO DIFFERENT VARIETIES OF Kappaphycus alvarezii - Sulaeman Sulaeman; Andi Parenrengi; Emma Suryati; Rosmiati Rosmiati (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2007)
Two different colors (green and brown) of Kappaphycus alvarezii have been farmed in Indonesian waters for many years. This study aimed at comparing two ‘varieties’, i.e. green and brown, both genetically and morphologically. Samples for DNA analysis were collected from a farmer in Pinrang Regency, South Sulawesi. Five universal primers i.e. Ca-01, Ca-02, P-40, P-50, and DALRP were selected to obtain DNA genetic markers in differentiating the green and brown varieties. To compare coloration patterns during cultivation and the growth performance of both varieties, a field experiment was performed in a seaweed farming area in Pinrang Regency, during dry season of August-September 2004. The result of genetic assessment showed that the five selected primers revealed different RAPD banding pattern for both varieties. P-50 and DALRP primers demonstrated the greatest amplification in differentiating RAPD fragment between green and brown varieties. Fragment 900 bp and 1.300 bp were consistently generated in the green variety but were not amplified in the brown variety. The result of the field study confirmed that the coloration pattern of green and brown varieties was fixed; no interchange in color occurred during one crop cultivation.